Agricultural public expenditures, sector performance, and welfare in Nigeria: A state-level analysis - Mavrotas, George; Mogues, Tewodaj; Oyeyemi, Motunrayo; Smart, Jenny; Xiong, Zhe (International Food Policy Research Institute, 2018)
Building on the work of earlier studies that looked at trends in and returns to federal public expenditures on agriculture in Nigeria, this paper explores spending patterns at the sub-national state level over a nine-year period, as well as trends in agricultural and economic performance and indicators of household welfare. Our examination focuses on two groupings of states – the full 37 state units of Nigeria (the 36 states, plus the Federal Capital Territory, Abuja); and the seven states that are the focus in Nigeria of the Global Food Security Strategy (GFSS) of the United States Agency for International Development. Sub-national agricultural spending as a share of aggregate agricultural spending in Nigeria is large, given the stronger role for sub-national governments in agriculture than is the case in other sectors. However, we find that the share of state-level expenditures on agriculture as a share of aggregate state-level expenditures is still relatively low, an average of 3.86 percent over the period 2007 to 2015. While the prioritization of agriculture spending varies greatly year by year, the variation over time does not have a discernible long-run upwards or downwards trend. We also find that agricultural expenditures are more capital intensive than are overall public expenditures at state level, but that capital expenditures as a share of total agriculture spending has decline over the last decade, as is the case overall in Nigeria’s industrial sectors. We conclude that efforts to strengthen state-level agricultural spending in Nigeria merits greater attention, while putting in place measures to ensure improved effectiveness in any such spending.